PARAMETERS EVALUATION AND DETERMINATION OF REPRODUCTIVES WISTAR RATS (Mus norwergicus albinus) UNDER AVERMECTINS TREATMENT - FOLADOR, Alessandra (Scientia Agraria, 2000)
Avermectins are widely used to treat endo and ectoparasitoses. The effect of such drug on male reproductive system is poorly studied. Our research aimed to study if the avermectins abamectin, doramectin and ivermectin would have any effect on organs, tissues and hormones involved in the reproduction. Male Wistar rats were treated with each different avermectins in the dose of 1 mg/kg, subcutaneously, and in the control was administered the vehicle. The animals were sacrified in the 1st, 3rd 5th and 8th week post inoculation of the drug morphological and biochemical parameters were evaluated. The testes, prostate, seminal vesicles, epididymis and hipophysis mass were not different between the groups in whole period studied. Analysis of motility, vigor sperm morphology and the histology of testicular parenchyma did not detect any aberration as compared to control in the weeks studied. The epididymis content submitted to SDS-PAGE did not reveal any alteration on the electrophoresis of proteins between the studied groups compared to control. The biochemical serum measurements of glycemia, LH, FSH hormones and total testosterone also not shown any difference between the experimental and control groups. The responsiveness of testicular parenchyma incubated with hCG were investigated by testosterone production and there was no difference in all groups studied. The data about the mass weight evolution showed gain in the body weight identical to the control group, except in the ivermectin group, which had a significant increase in the body weight (p